Movimentos sociais e políticas públicas LGBTI+: análise dos efeitos dos movimentos sociais no desenho de políticas públicas voltadas para diversidade sexual e de gênero na Paraíba - Lins, Ingrid Raíssa Guerra (2023)
The present study aims to analyze the effects of the LGBTI+ social movement on the formulation of public policies addressing sexual diversity and gender in Paraiba, Brazil. In recent years, there have been processes of achievements and setbacks in federal LGBT policies. The experiences of the Workers’ Party (PT), particularly during Lula’s government, have introduced new patterns of socio-state interactions that impacted the relations among social and state actors. In light of this, the LGBT+ movement has occupied institutional spaces and pushed forward their demands in collaboration with state actors. The investigation found that the LGBTI+ movement and the government of Paraiba have operated in a similar manner. Therefore, using the concepts of repertoires and institutional fit, the mutually constituted public policies in Paraiba are analyzed. Given the above, the research is an exploratory case study, employing several qualitative methods, such as a literature review, document analysis and semi-structured interviews with local actors, and utilizing content analysis to collect the necessary data. The main finding indicates that demands and policies are strengthened when actors interact cooperatively in the formulation and implementation of their own public policies.